Use of rice flour in wheat bread technology - Shevchenko, Anastasiia; Drobot, Vira (My University, 2022)
Last decade is characterized by the increase in the incidence of inflammatory bowel diseases all over the world. Diet therapy, which includes reducing the amount of dietary fiber and including phospholipids in it, is effective in maintaining a stable condition in case of these diseases. A promising raw material with a low dietary fiber content is rice flour, which may be added to the recipe of bakery products to replace part of wheat flour. The aim of the work was to determine the influence of rice flour on the course of the technological process and the characteristics of the dough in bakery products manufacturing, as well as on the quality indicators of bread made from wheat flour, which contains lecithin. Rice flour contains 1.8 times less protein than wheat flour, but this protein is more complete in amino acid composition. The content of dietary fibers in rice flour is 8.5 times lower. The gas-forming capacity of the dough with lecithin separately and in a mixture with rice flour increases by 8.4−18.7 % when replacing 10−40 % of wheat flour. It was established that in the dough sample with lecithin, the amount of formed and fermented sugars increased by 1.2 % and 12.1 %, respectively, compared to the control sample without additives. With an increase in the percentage of replacement of wheat flour with rice flour, the amount of formed sugars increased by 35.2−39.0 %. The amount of fermented sugars also increased by 19.6−31.8 % with an increase in the percentage of replacement. The shape stability of bread slightly improved with the addition of lecithin. However, when adding rice flour, the shape stability of the products decreased by 7.1−26.8 %, as well as the specific volume and porosity of bread.
Keywords: rice flour; lecithin; gas formation capacity; dough; bakery product; kinetics of sugars; кафедра технології хлібопекарських і кондитерських виробів